Sexual-lineage-specific DNA methylation regulates meiosis in Arabidopsis. (January 2018) - Walker, James; Gao, Hongbo; Zhang, Jingyi; Aldridge, Billy; Vickers, Martin; Higgins, James; Feng, Xiaoqi
Abstract DNA methylation regulates eukaryotic gene expression and is extensively reprogrammed during animal development. However, whether developmental methylation reprogramming during the sporophytic life cycle of flowering plants regulates genes is presently unknown. Here we report a distinctive gene-targeted RNA-directed DNA methylation (RdDM) activity in theArabidopsis thaliana male sexual lineage that regulates gene expression in meiocytes. Loss of sexual-lineage-specific RdDM causes mis-splicing of theMPS1 gene (also known asPRD2 ), thereby disrupting meiosis. Our results establish a regulatory paradigm in which de novo methylation creates a cell-lineage-specific epigenetic signature that controls gene expression and contributes to cellular function in flowering plants. RNA-directed DNA methylation (RdDM) in theArabidopsis thaliana male sexual lineage is shown here to regulate gene expression in meiocytes. Loss of sexual-lineage-specific RdDM causes mis-splicing of theMPS1 gene, thereby disrupting meiosis